Effect of inhalation exposure to toluene on the activity of organic anion transporting polypeptide (Oatp) using pravastatin as a probe drug in rats - Mauro, Mariana [UNESP]; Lepera, Jose Salvador [UNESP]; Borsari, Bruno [UNESP]; Capela, Jorge Manuel Vieira [UNESP]; de Moraes, Natália Valadares [UNESP] (Taylor & Francis, 2018)
1. Toluene, used as a pure substance or in solvent mixtures, is the cause of occupational exposures of large numbers of workers in the world. The organic anion transporting polypeptides (OATP: human; Oatp: rodents) are drug carriers which have been frequently associated to drug–drug interactions. The objective of this study was to evaluate the influence of inhalation exposure to toluene in Oatp in vivo activity using pravastatin as a probe drug in rats. 2. Male Wistar rats ((n = 6 per sampling time) were exposed to 85 mg/m3 toluene by inhalation or air in a nose only exposure system for 6 h/d, 5 d/week during 4 weeks, in order to simulate the occupational exposure to toluene at level slightly above the occupational exposure limit proposed by the American Conference of Governmental Industrial Hygienists (ACGIH). After 4 weeks of exposure, animals received a single dose of 20 mg/kg pravastatin orally. 3. Areas under concentration × time curves extrapolated to infinite (AUC0–∞) were calculated by Gauss Laguerre quadrature. Non-exposed animals showed AUC0–∞ of 726.0 (261.8) ng h/mL for pravastatin and rats exposed to toluene 85 mg/m3 showed AUC0–∞ of 681.8 (80.1) ng h/mL [data presented as mean (standard error of the mean)]. No significant difference was observed in pravastatin kinetic disposition between groups in terms of 95% confidence interval for the difference between means. 4. Toluene exposure by inhalation did not change the in vivo activity of Oatp evaluated by pravastatin kinetic disposition in rats.
Keywords: Clearance; drug transporter; nose only exposure system; occupational exposure; statin